Nanomaterial Nitric Oxide Delivery in Traumatic Orthopedic Regenerative Medicine - Anastasio, Albert Thomas; Paniagua, Ariana; Diamond, Carrie; Ferlauto, Harrison R.; Fernandez-Moure, Joseph S. (Frontiers in Bioengineering and Biotechnology, 2021)
Achieving bone fracture union after trauma represents a major challenge for the orthopaedic surgeon. Fracture non-healing has a multifactorial etiology and there are many risk factors for non-fusion. Environmental factors such as wound contamination, infection, and open fractures can contribute to non-healing, as can patient specific factors such as poor vascular status and improper immunologic response to fracture. Nitric oxide (NO) is a small, neutral, hydrophobic, highly reactive free radical that can diffuse across local cell membranes and exert paracrine functions in the vascular wall. This molecule plays a role in many biologic pathways, and participates in wound healing through decontamination, mediating inflammation, angiogenesis, and tissue remodeling. Additionally, NO is thought to play a role in fighting wound infection by mitigating growth of both Gram negative and Gram positive pathogens. Herein, we discuss recent developments in NO delivery mechanisms and potential implications for patients with bone fractures. NO donors are functional groups that store and release NO, independent of the enzymatic actions of NOS. Donor molecules include organic nitrates/nitrites, metal-NO complexes, and low molecular weight NO donors such as NONOates. Numerous advancements have also been made in developing mechanisms for localized nanomaterial delivery of nitric oxide to bone. NO-releasing aerogels, sol- gel derived nanomaterials, dendrimers, NO-releasing micelles, and core cross linked star (CCS) polymers are all discussed as potential avenues of NO delivery to bone. As a further target for improved fracture healing, 3d bone scaffolds have been developed to include potential for nanoparticulated NO release. These advancements are discussed in detail, and their potential therapeutic advantages are explored. This review aims to provide valuable insight for translational researchers who wish to improve the armamentarium of the feature trauma surgeon through use of NO mediated augmentation of bone healing.